RESPON PERTUMBUHAN KACANG TANAH (Arachis hypogaea L.) PADA BERBAGAI DOSIS BOKASHI LIMBAH AMPAS TAHU DAN PUPUK FOSFAT - KURNIAWAN, IRWAN; AFA, LAODE; YUSUF, DEWI NURHAYATI (Jurnal Agroteknos, 2022)
Peanut (Arachis hypogaea L.) is an agricultural commodity that acts as a protein and vegetable oil source, but in Southeast Sulawesi, its productivity is still relatively low. This study aims to determine the effect of giving bokashi tofu waste and phosphate fertilizer on the growth of peanut plants. The research was conducted at the Experimental Field Laboratory II, Faculty of Agriculture, Halu Oleo University, Kendari, from June to September 2021. The study used a factorial randomized block design consisting of bokashi tofu waste with four treatment levels, namely 0, 5, 10, and 15 tons per hectare, and phosphate fertilizers with three treatment levels, namely 0, 100, and 200 kg per hectare. The total combination of treatments was 12, with three replications. Observational data were analyzed using analysis of variance and UJBD. The analysis results showed that the interaction of bokashi with tofu waste and phosphate fertilizer had a significant effect on plant heights 28 and 35 DAP, stem diameter 21 DAP, leaf area 14, 21, and 28 DAP, and root loss ratio. Bokashi tofu waste independently significantly affected plant height, stem diameter 28 DAP, leaf area, and root loss ratio. Phosphate fertilizer independently significantly affected plant height at 28 and 35 DAP, leaf area at 14 and 21 DAP, and root loss ratio. The combination of 15 tons of tofu waste bokashi per hectare and 100 kg of phosphate fertilizer per hectare was the best treatment for increasing the growth of peanut plants.